Pemanfaatan Media Video dalam Meningkatkan Minat dan Hasil Belajar Siswa SD - Khairotul Nur Indah .W; Suci Febrianti; Indah Rahmi Rahmadani; Yarisda Ningsih; Nur Azmi Alwi (Politeknik Kampar, 2025)
This article reviews the use of video media as one approach to improve the interest and learning achievement of elementary school students. In the midst of the development of the digital era, technology-based learning media such as video is an efficient solution in delivering material in an interesting and interactive way. This study was conducted through a literature review of various sources that discuss the effectiveness of video media in the learning process at the elementary school level. Based on the results of the study, it is known that video media is able to attract students' attention and contribute to improving conceptual understanding and memory of the material. Therefore, it is recommended that educators utilize video media as a tool in teaching and learning activities to enrich students' learning experiences.